2001
DOI: 10.1034/j.1600-0609.2001.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascularization in myeloma

Abstract: Several studies have shown that the number of intratumoral vessels can predict the aggressiveness of a solid cancer, development of metastases and patient survival. Does angiogenesis play an important role in myeloma? The aim of our study was to quantify bone marrow vascularity in various stages of proliferative plasma cell disorders (monoclonal gammopathies of undetermined significance (MGUS), stage I multiple myeloma (MM), stage III MM and Waldenström's macroglobulinemia (WM)) and to compare it with that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated the presence of increased bone marrow angiogenesis in patients with multiple myeloma (Vacca et al , 1994; Rajkumar et al , 1999a; Ahn et al, 2001; Laroche et al, 2001). It continues to be debated whether this finding is related to the pathogenesis of the disease or whether it is merely an epiphenomenon or a surrogate marker of other biological features that are important in myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of increased bone marrow angiogenesis in patients with multiple myeloma (Vacca et al , 1994; Rajkumar et al , 1999a; Ahn et al, 2001; Laroche et al, 2001). It continues to be debated whether this finding is related to the pathogenesis of the disease or whether it is merely an epiphenomenon or a surrogate marker of other biological features that are important in myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3, 4 There is a direct correlation between BM microvessel density and parameters of disease progression. 5 Moreover, increased BM vascularization in MM patients is correlated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on non-solid tumors, different authors have reported altered angiogenesis in association with different hematological malignancies. Laroche et al reported that the number of arterioles and capillaries increased in myeloma from its initial stages according to the gravity of the disease [ 119 ]. Increased BM angiogenesis and increased levels of associated factors, such as VEGF, have also been described in relation to AML, ALL, B-CLL or CML, among others, leading to the development of therapeutic applications based on disruption of this mechanism [ 120 ].…”
Section: Unresolved Questions In Modeling Bm and Non-solid Tumorsmentioning
confidence: 99%